2018
DOI: 10.1007/s00380-018-1215-4
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter trial of extracorporeal cardiac shock wave therapy for refractory angina pectoris: report of the highly advanced medical treatment in Japan

Abstract: We have previously demonstrated that cardiac shock wave therapy (CSWT) effectively improves myocardial ischemia through coronary neovascularization both in a porcine model of chronic myocardial ischemia and in patients with refractory angina pectoris (AP). In this study, we further addressed the efficacy and safety of CSWT in a single-arm multicenter study approved as a highly advanced medical treatment by the Japanese Ministry of Health, Labour and Welfare. Fifty patients with refractory AP [mean age 70.9 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…The number of studies included involving LVEF were 12 [ 4 , 9 , 11 , 12 , 16 - 18 , 20 , 21 , 24 , 27 , 29 ] , with a total of 566 patients. The included study types were nine single-arm studies, two cohort studies, and one RCT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of studies included involving LVEF were 12 [ 4 , 9 , 11 , 12 , 16 - 18 , 20 , 21 , 24 , 27 , 29 ] , with a total of 566 patients. The included study types were nine single-arm studies, two cohort studies, and one RCT.…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies included involving SDS were two [ 4 , 6 ] , with a total of 306 patients. These were single-arm studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A data from both small randomized-controlled trials and real-world experiences confirmed the efficacy of ESMR in terms of symptom improvement, reduced use of short-acting nitrates and hospitalizations, increased myocardial perfusion at different follow-up periods up to 72 months in patients with stable CAD and specifically RA patients [ 66 , 67 , 68 , 69 , 70 , 71 ]. A prospective controlled study of 72 RA patients showed improved symptoms and quality of life parameters, increased myocardial perfusion at six months [ 67 ] with sustained effect at a longer time period (2.88 ± 1.65 years) [ 68 ].…”
Section: Extracorporeal Shockwave Myocardial Revascularizationmentioning
confidence: 84%
“…Mechanical stimulation, or, for example, shock waves, have been known for their beneficial effect in various medical conditions to stimulate angiogenesis [ 105 , 106 ], in the field of cardiac regeneration [ 107 , 108 ] or to steer the inflammatory response [ 109 ]. Comparable investigations on sound-induced effects are currently lacking and need to be further investigated.…”
Section: Acoustic Patterning On Different Timescalesmentioning
confidence: 99%